Kombinasi Madu dan Patikan Kerbau (Euphorbia hirta L.) pada Berbagai Kombinasi dalam Mengobati Ikan Mas (Cyprinus carpio) yang Sakit - Natonis, Olga Fransina; Salosso, Yuliana; Santoso, Priyo (Jurnal Aquatik, 2025)
Carp (Cyprinus carpio) is a freshwater fishery commodity that has significant economic value and high development prospects. This species is widely cultivated due to increasing market demand, thus offering great opportunities for development in intensive and semi-intensive cultivation systems. This study used a completely randomized design (CRD) with 3 treatments and 3 replicates. The parameters measured included survival rate (SR) and growth. Survival rate data were statistically analyzed at a predetermined significance level and followed by a BNT test according to the Steel and Torrie method. The results showed that the administration of spurge extract (Euphorbia hirta L.) did not have a significant effect on the survival rate of carp (Cyprinus carpio). The administration of spurge extract (Euphorbia hirta L.) at a concentration of 12.5 mg/L resulted in an average value of 80%. In comparison, the administration of a 25 mg/L concentration of Euphorbia hirta L. extract resulted in an average value of 93.33%. The administration of 37.5 mg/L of Euphorbia hirta L. extract resulted in an average value of 86.66%. Based on this presentation, it can be said that Euphorbia hirta L. extract affects the survival of carp (Cyprinus carpio).